2018
DOI: 10.1113/jp275856
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular dysfunction in metabolic syndrome

Abstract: Metabolic syndrome is a critically important precursor to the onset of many diseases, such as cardiovascular disease, and cardiovascular disease is the leading cause of death worldwide. The primary risk factors of metabolic syndrome include hyperglycaemia, abdominal obesity, dyslipidaemia, and high blood pressure. It has been well documented that metabolic syndrome alters vascular endothelial and smooth muscle cell functions in the heart, brain, kidney and peripheral vessels. However, there is less information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 264 publications
(222 reference statements)
2
12
0
Order By: Relevance
“…This result is consistent with the findings of Ouerghi et al and Nikseresht who reported that the serum level of insulin in inactive obese men was significantly higher than lean men [5,6]. Moreover, Kadoglou et al concluded that insulin resistance index in active patients was significantly lower than that of inactive patients [11].…”
Section: Qazvin University Of Medical Sciencessupporting
confidence: 91%
“…This result is consistent with the findings of Ouerghi et al and Nikseresht who reported that the serum level of insulin in inactive obese men was significantly higher than lean men [5,6]. Moreover, Kadoglou et al concluded that insulin resistance index in active patients was significantly lower than that of inactive patients [11].…”
Section: Qazvin University Of Medical Sciencessupporting
confidence: 91%
“…The association between an elevated PAAr and an FEV 1 < LLN may be related to distal vasculopathy, as previously suggested, and could be similar to what has been described in smokers with or without significant emphysema . Although that could result from toxicant induced injury, as has been proposed for tobacco related chronic obstructive pulmonary disease, another potential explanation is that increased PAAr reflects obesity (with or without metabolic syndrome) associated pulmonary hypertension, and a post hoc analysis showed that PAAr was significantly associated with obesity (data not shown). Our studies in this cohort have demonstrated the adverse effect of obesity and weight gain on longitudinal follow up, the prevalence of obesity and the metabolic syndrome is known to be substantial in this cohort, and a case‐control study among WTC firefighters demonstrated associations of metabolic syndrome biomarkers with adverse respiratory outcomes (FEV 1 % less than predicted lower limit of normal) …”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the present study group did not include any subject with that type of disease. Despite the richness of our data and the good overall performance of our model, we lacked information on other factors that can relate to airway disease outcomes, like atopy, pre‐WTC occupational exposures, smoking intensity, and smoking status after baseline, or on pulmonary vascular disease, such as metabolic syndrome components other than obesity . Previous studies, however, have not suggested an association between atopy and WTC lower airway disease, and occupational airway disease and periodic cross‐sectional assessments of smoking status in this cohort do not suggest increasing group smoking rates (data not presented).…”
Section: Discussionmentioning
confidence: 88%
“…Rodent models of obesity and diabetes demonstrate that hyperglycemia increases pulmonary vascular permeability, inflammation, and remodeling that may exacerbate COVID‐19 lung inflammation (23). Mouse models suggest that circulating factors from obese mice and free fatty acids upregulate endothelial cell adhesion molecules and worsen lipopolysaccharide‐induced ALI potentially through endoplasmic reticulum stress (24).…”
Section: Dysregulated Pulmonary Responses To Infection In Obesitymentioning
confidence: 99%